Effect of Purslane (Portulaca oleracea L.) Ethanol Extract in Alloxan-induced Hyperglycemic Rats (Rattus novergicus L.) Blood Glucose Levels - Anastasia Sylvianka Dwi Jayanti; Agung Janika Sitasiwi; Sri Isdadiyanto (Jurnal Sain Veteriner, 2022)
Diabetes mellitus (DM) is a chronic condition which caused by insulin secretion disorder, insulin resistance or both. High number of diabetics per year has led many researchers to conduct research to find the most safe and effective medicine for DM treatment. Flavonoid are known to act as inhibitors of α-amylase as a parameter of pancreatic damage and help lower blood glucose levels. One source of flavonoids is purslane. The aim of this study was to examine the effect of purslane ethanol extract on glucose and α-amylase levels in rat. Twenty rats Rattus novergicus L. strain Wistar are divided into 5 groups; control, positive control, and three test groups, each was given purslane ethanol extract of 100 mg/kgBW, 200 mg/kgBW, and 300 mg/kgBW. Blood glucose and body weight were measured before alloxan induction, after induction, as well as day- 7, 14, 21, and 28; while feed and drink consumption were measured everyday starting with the administration of purslane ethanol extract. The α-amylase test was carried out on the 28th day using enzymatic UV determination of degradation product of maltose and glucose method. The analysis result showed that rats blood glucose and α-amylase decreased in each group with purslane extract. The antioxidant content of flavonoids in purslane ethanol extract has been shown to have anti-diabetic effects by repairing pancreatic function.